Influence of crop residue, flyash and varying starter dosages on growth, yield and soil characteristics in rice (Oryza sativa)-wheat (Triticum aestivum) cropping system under irrigated conditions of Jammu region - KACHROO, DILEEP; DIXIT, ANOOP KUMAR; BALP, AMARJIT S (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during rainy (kharif) 2001 winter season (rabi) 2002 at research farm of the University at Jammu to evaluate the influence of residue incorporation on the productivity and soil health in rice (Oryza sativa L.)-wheat (Triticum aestivuln L. emend Fiori & Pao!.) cropping system under irrigated conditions. Incorporation of rice residues in wheat and wheat residues in rice not only increased the productivity of system (16.20/0) and yield conlponents of rice and wheat but also increased the nutrient uptake (18.5 kg nitrogen, 3.6 kg phosphorus and 19.6 kg potassiulu/ha) compared to without residue incorporation besides improved the physico-chemical and microbiological properties of the soil. Alternatively the incorporation of flyash and left over stubbles of previous crops as residues were equally found effective in increasing the productivity by 13.5 ’and 8.1 %, respectively and soil environment in rice-wheat cropping system over without residue incorporation. Application of Trichodenna viride + 20 kg N/ha or fannyard manure (5 tonnes/ha) as starter dose for quick and better decomposition showed to influence the yield; nutrient uptake, available nutrients status, microbial population and physical properties of the soil significantly than no starter dose application.